2010
DOI: 10.1037/a0020524
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical and empirical review of the death-thought accessibility concept in terror management research.

Abstract: Terror management theory (TMT) highlights the motivational impact of thoughts of death in various aspects of everyday life. Since its inception in 1986, research on TMT has undergone a slight but significant shift from an almost exclusive focus on the manipulation of thoughts of death to a marked increase in studies that measure the accessibility of death-related cognition. Indeed, the number of death-thought accessibility (DTA) studies in the published literature has grown substantially in recent years. In li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
270
2
12

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 311 publications
(304 citation statements)
references
References 147 publications
8
270
2
12
Order By: Relevance
“…TMT has inspired considerable research suggesting, for example, that reminders of mortality motivate people to identify with their cultural beliefs and strive to enhance their selfworth, and that defense of these structures then reduces cognitions about mortality (see e.g., Greenberg, 2015, andHayes, Schimel, Arndt, &Faucher, 2010 for conceptual reviews; Burke, Martens, &Faucher, 2010 andSteinman &Updegraff 2015 for metaanalytic reviews). However, despite the many different directions of terror management research, very little work has examined heroism.…”
Section: Terror Management Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…TMT has inspired considerable research suggesting, for example, that reminders of mortality motivate people to identify with their cultural beliefs and strive to enhance their selfworth, and that defense of these structures then reduces cognitions about mortality (see e.g., Greenberg, 2015, andHayes, Schimel, Arndt, &Faucher, 2010 for conceptual reviews; Burke, Martens, &Faucher, 2010 andSteinman &Updegraff 2015 for metaanalytic reviews). However, despite the many different directions of terror management research, very little work has examined heroism.…”
Section: Terror Management Theorymentioning
confidence: 99%
“…DTA was assessed after the writing task with a word fragment completion task used in many previous TMT studies (Hayes et al, 2010). Participants completed 25 word fragments, 7 of which could be completed with either a death-related word or a non-death word (e.g., the fragment CO_ _ _ _ could be completed as COFFIN [a death-related word] or as COFFEE [a non-death word]).…”
Section: Very Heroic)mentioning
confidence: 99%
See 1 more Smart Citation
“…Reminding participants of their mortality leads to support for more restrictive punishment for a man who left his wife and children (Oschmann & Reichelt, 1994 as reported in Pyszczynski et al, 1997), a person accused of prostitution (Rosenblatt, Greenberg, Solomon, Pyszczynski, & Lyon, 1989), perpetrators of various moral offenses (Florian & Mikulincer, 1997), as well as to greater respect for cultural symbols (Greenberg, Porteus, Simon, Pyszczynski, & Solomon, 1995) increased prosocial behavior, especially towards charities aiding one's own culture (Jonas, Schimel, Greenberg, & Pyszczynski, 2002) and attributed stronger humanness to the ingroup (Vaes, Goldenberg, Heflick (2010). The recent review of research on TMT presents Hayes et al (2010) and Lukaszewski (2010) in Polish literature.…”
Section: Empirical Support For Tmtmentioning
confidence: 99%
“…For example, some studies have shown that other types of psychological threats such as thoughts of being uncertain (van den Bos and Miedema, 2000) or not having control (Fritsche et al, 2008) can cause effects similar to reminders of mortality. Yet, there seems to be still a larger body of empirical work advocating for unique and specific effects of thinking about death (Hayes et al, 2010 andBurke et al, 2010 for a metanalytic assessment).…”
Section: "I'm Not Afraid Of Death; I Just Don't Want To Be There Whenmentioning
confidence: 99%